Megascolex (Promegascolex) mekongianus Cognetti, 1922 - its extent, ecology and allocation to Amynthas (Clitellata/Oligochaeta: Megascolecidae) - Blakemore, R.J.; Csuzdi, Cs.; Ito, M.T.; Kaneko, N.; Paoletti, M.G.; Spiridonov, S.E.; Uchida, T.; Van Praahg, B.D. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2007)
Cognetti (1922) miscounted segments of his Megascolex (Promegascolex) mekongianus and, believing the gizzard in 7 was intermediate between Megascolex, with gizzard in 5, and Pheretima, with gizzard after 7/8, he proposed the subgenus Promegascolex. Next, Gates (1934: 260) redescribed the immature, poorly preserved and abnormal type as Pheretima mekongiana. However, Sims & Easton (1972: 223) listed it as species incertae sedis, excluded it from their Pheretima-group of genera and postulated its gizzard was “clearly in segment 5”. The latter authors also mistook the River Mekong, “Annam” type locality as “Vietnam”. Recently collected material from the River Mekong in Laos is herein described that complies with the corrected type description allowing new designation as Amynthas mekongianus comb. nov. Moreover, A. fluvialis (Gates, 1939) from the Mekong in Thailand is found to be a synonym, although Metaphire fluvialoides (Huynh Thi Kim Hoi, 1998) comb. nov. from Central Highlands of Vietnam remains separate. Reallocation of the type species adds Promegascolex as syn. nov. to Amynthas and its generic diagnosis is amended from Sims & Easton (1972: 211) to permit: Clitellum annular, 14-16, rarely beginning on 13, sometimes extending into 17 (e.g. in A. mekongianus). The slender length and annulations of current specimens: measuring up to 2,900 mm with more than 500 segments, are near the maxima recorded for any earthworm; comparisons are given with “giants” in various families from other regions of the World. Brief comments are made on diversity and ecology of the River Mekong locality.